2022
DOI: 10.1186/s13568-022-01406-w
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization, antimicrobial, antioxidant, and cytotoxic potentials of Swietenia mahagoni

Abstract: Infectious diseases are the most important cause of death worldwide. Many of these diseases show great resistance to drugs and antibiotics with long-term use. Extracts of some medicinal plants have antimicrobial properties, which can treat and overcome these diseases. Meliaceae is a family of timber trees used extensively in treating many bacterial and fungal diseases, especially Swietenia mahagoni (L.) Jacq. In this study, phytochemical screening, gas chromatography/mass spectrometry (GC/MS) analysis, and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
2
3
0
1
Order By: Relevance
“…However, less activity was observed at a concentration of 15 mg•mL −1 , with IZ ranging from 9.5 to 13.1 mm. Conversely, no antifungal activity was observed against A. fumigatus and C. glabrata [44]. However, our promising antifungal results are consistent with those obtained by previous studies, which showed that the methSM extract was effective against C. albicans and A. niger at a concentration of 100 mg•mL −1 , with IZ ranging from 16 to 20 mm [20].…”
Section: Discussionsupporting
confidence: 91%
“…However, less activity was observed at a concentration of 15 mg•mL −1 , with IZ ranging from 9.5 to 13.1 mm. Conversely, no antifungal activity was observed against A. fumigatus and C. glabrata [44]. However, our promising antifungal results are consistent with those obtained by previous studies, which showed that the methSM extract was effective against C. albicans and A. niger at a concentration of 100 mg•mL −1 , with IZ ranging from 16 to 20 mm [20].…”
Section: Discussionsupporting
confidence: 91%
“…MIC wells were sub‐cultured in order to determine MBC and MFC. The MBC and MFC values indicated the lowest concentrations of the EO that did not exhibit any microbial growth [96,97] …”
Section: Methodsmentioning
confidence: 99%
“…The MBC and MFC values indicated the lowest concentrations of the EO that did not exhibit any microbial growth. [96,97] Free radical scavenging Assessments…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The change in colour of 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) from deep violet to pale yellow was monitored spectrophotometrically at a wavelength of 517 nm for 3 h. The scavenging effect was calculated using the expression in Eq. 4 (Syame et al 2022 ). …”
Section: Methodsmentioning
confidence: 99%